2022
DOI: 10.1093/socpro/spac001
|View full text |Cite
|
Sign up to set email alerts
|

Leaving the Pervasive Barrio: Gang Disengagement under Criminal Governance

Abstract: Is it possible to disengage from street gangs in communities and districts where gang organizations rule? We argue that disengagement is possible when this process does not alter the social order that allows street gangs to continue controlling and establishing the rules that govern economic activities and relationships in the barrios they control. We explore the process of gang disengagement under criminal governance in El Salvador, a country plagued by the powerful MS-13 and Barrio 18 gangs. We conducted a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Disengagement may be entangled in personal processes of religious conversion. In contrast to the literature that underscores the motives to leave the gang through the processes of personal change, however, several gang members choose religious restoration because it is the only path available to them in contexts when gangs rule with the collaboration of churches (Cruz & Rosen, 2022;Offutt, 2019). The former does not mean that the identity transformations afforded by religion are false (Maruna et al, 2006).…”
Section: Disengagement Under Gang Governancementioning
confidence: 91%
See 1 more Smart Citation
“…Disengagement may be entangled in personal processes of religious conversion. In contrast to the literature that underscores the motives to leave the gang through the processes of personal change, however, several gang members choose religious restoration because it is the only path available to them in contexts when gangs rule with the collaboration of churches (Cruz & Rosen, 2022;Offutt, 2019). The former does not mean that the identity transformations afforded by religion are false (Maruna et al, 2006).…”
Section: Disengagement Under Gang Governancementioning
confidence: 91%
“…We build these insights based on a comparative case study with 112 in‐depth interviews with former gang members in El Salvador, Guatemala, and Honduras. We propose this theory of gang disengagement based on a multiyear research effort that has shown the importance of group processes, social factors, and religious affiliation in gang disengagement in Central America (Cruz & Rosen, 2020, 2022; Rosen & Cruz, 2018). This article, however, advances our scholarship and presents a novel model that explains the modes of gang disengagement based on the ruling capabilities of the criminal group.…”
mentioning
confidence: 99%
“…Notably, a significant portion of this population resides in urban settings, which suggests that greater state presence does not necessarily correlate negatively with the strength of OCGs. 39 Such governance is exercised by large drug cartels, 40 street gangs 41 and prison gangs alike. 42 Given this variety of OCGs, the way they govern is also multifaceted.…”
Section: Criminal Governancementioning
confidence: 99%